Evaluasi Pemanfaatan Ruang Tahun 2013-2014Terhadap Rencana Detil Tata Ruang (Rdtr) Kecamatan Jogonalan Tahun 2013-2018 - Susilo, Wijanarko Noor Imam (2016)
Jogonalan sub-districts of Klaten district is an area of study in this research . The purpose of this study were ( 1 ) Evaluate the suitability of the use of space in 2013-2014 to the Detailed Spatial Plan for the year 2013-2018 the District Jogonalan ( 2 ) Evaluate the types of irregularities utilization of space in 2013-2014 to the Detailed Spatial Plan for the year 2013-2018 the District Jogonalan. The method used in this study are ( 1 ) test the accuracy of the map data to field checks (survey ) that checks the field is done to match the map data space utilization latest available with the real situation in the field along with documentation shape the utilization of space in the field, so it can be used to test accuracy / precision in 2014 ( 2 ) analysis of secondary data from relevant agencies using overlay analysis with the help of Geographic Information System ( GIS ) to determine the suitability of space utilization and the type of spatial irregularities done. Results from this study is the use of space Conformity District of Jogonalan appropriate classification level which is the largest village in the village Dompyongan dominated by 92.51% or 171.57 ha of area 185.45Ha, the classification is not appropriate in the village Plawikan in the amount of 40.28 hectares or 29.84% of the total 135.01 ha and the classification is not appropriate in the village of 9.75Ha Granting that is equal to or 8:52% of the total 114.41 ha. The deviation types of spatial shown with a plan for food crops but the use of space in 2014, namely residential area of 15.71Ha or 21.75% are in the village kraguman, karangdukuh Village, Village Joton, Bakung village, Gondangan Village, and Village Sumyang. The smallest deviation types shown with a plan to train border but the use of space in 2014 tomb of 0.01ha or a 0.01% found in the village of Pakahan and the smallest deviation is indicated by the type of plan SUTT border but the use of space in 2014 tomb of 0.01ha or a 0.01% contained Village Rejoso.